Antibacterial properties of nitric oxide-releasing porous silicon nanoparticles. Issue 11 (2nd March 2016) - Hasanzadeh Kafshgari, M.; Delalat, B.; Harding, F. J.; Cavallaro, A.; Mäkilä, E.; Salonen, J.; Vasilev, K.; Voelcker, N. H.
Abstract : In this study, the antibacterial efficacy of NO-releasing porous silicon nanoparticles (pSiNPs) is reported. NO-releasing pSiNPs were produced via the conjugation of S -nitrosothiol (SNO) and S -nitrosoglutathione (GSNO) donors to the nanoparticle surfaces. Abstract : In this study, the antibacterial efficacy of NO-releasing porous silicon nanoparticles (pSiNPs) is reported. NO-releasing pSiNPs were produced via the conjugation of S -nitrosothiol (SNO) and S -nitrosoglutathione (GSNO) donors to the nanoparticle surfaces. The release of the conjugated NO caused by the decomposition of the conjugated SNO and GSNO was boosted in the presence of ascorbic acid. The released NO was bactericidal to Gram-positive ( Staphylococcus aureus ) and Gram-negative bacteria ( Escherichia coli ), and eliminated bacterial growth within 2 h of incubation without compromising the viability of mammalian cells. These results demonstrate the advantages of NO-releasing pSiNPs for antibacterial applications, for example, in chronic wound treatment.